2021
DOI: 10.1021/acs.organomet.1c00045
|View full text |Cite
|
Sign up to set email alerts
|

Methylene-Linked Bis-NHC Half-Sandwich Ruthenium Complexes: Binding of Small Molecules and Catalysis toward Ketone Transfer Hydrogenation

Abstract: The complex [Cp*RuCl(COD)] reacts with LH 2 Cl 2 (L = bis(3-methylimidazol-2-ylidene)) and LiBu n in tetrahydrofuran at 65 °C furnishing the bis-carbene derivative [Cp*RuCl(L)] (2). This compound reacts with NaBPh 4 in MeOH under dinitrogen to yield the labile dinitrogen-bridged complex [{Cp*Ru(L)} 2 (μ-N 2 )][BPh 4 ] 2 (4). The dinitrogen ligand in 4 is readily replaced by a series of donor molecules leading to the corresponding cationic complexes [Cp*Ru(X)(L)][BPh 4 ] (X = MeCN 3, H 2 6, C 2 H 4 8a, CH 2 CHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…The bis­(carbene) ligand MDI for the catalyst moiety was prepared by a coupling reaction of N -methylimidazole with dichloromethane following suitably adapted literature procedures, as shown in the Supporting Information, p S5. Deprotonation of the obtained ligand was performed with NaOH treatment at low temperature and the sequential addition of [Cp*Rh­(μ-Cl)­Cl] 2 , resulting in an air-stable reddish-orange powder in excellent yield. After repeated futile attempts to crystallize the resulting powder, a single crystal suitable for X-ray diffraction was obtained in a dichloromethane/diethyl ether system by a vapor diffusion method over 2 days after anion exchange with NH 4 PF 6 .…”
Section: Resultsmentioning
confidence: 99%
“…The bis­(carbene) ligand MDI for the catalyst moiety was prepared by a coupling reaction of N -methylimidazole with dichloromethane following suitably adapted literature procedures, as shown in the Supporting Information, p S5. Deprotonation of the obtained ligand was performed with NaOH treatment at low temperature and the sequential addition of [Cp*Rh­(μ-Cl)­Cl] 2 , resulting in an air-stable reddish-orange powder in excellent yield. After repeated futile attempts to crystallize the resulting powder, a single crystal suitable for X-ray diffraction was obtained in a dichloromethane/diethyl ether system by a vapor diffusion method over 2 days after anion exchange with NH 4 PF 6 .…”
Section: Resultsmentioning
confidence: 99%
“…While there is a report referring to the effect of the alkali-metal cations within the base on the rate of TH, 31 no significant difference is observed here between KOH and NaOH, which is consistent with similar Ru-NNN complexes published by Chen and Wang. 32,33 A selection of other bases showed much poorer performance (entries [12][13][14][15][16]. Varying the amount of catalyst from 0.5 mol % to 5 mol % revealed that catalyst efficiency peaked at 1 mol % catalyst, before dropping dramatically at 5 mol % (entries [17][18][19].…”
Section: Transfer Hydrogenation Optimisationmentioning
confidence: 99%
“…1 Among various transition metals catalysts used in this reaction, such as Fe, 2,3 Ru, 4,5 Os, 6 Co, 7,8 Rh, 9 Ir, 10 Ni, 11 Pd, 12 and Au, 13 Ru(II) complexes are one of the most efficient class of catalysts. 14,15 The effect of the ligands in the Ru(II) complexes plays a crucial role toward both selectivity and activity of the catalyst. 1 Following the successful of 1,2-diamines in Noyori-type catalysts for TH of carbonyl compounds, 16 Ru(II) complexes bearing alternative N-based donor ligands have been investigated for their catalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…To address the balance of advantages and drawbacks in NHC-analogues of xantphos, we have prepared ruthenium­(II) complexes of a new xanthene-(NHC) 2 ancillary ligand and tested examples as catalysts for the transfer hydrogenation of ketones and the selective electrochemical reduction of CO 2 to CO, as is reported herein.…”
Section: Introductionmentioning
confidence: 99%